Four Standardized Patient Cases for the Infectious Diseases Fellow - Anna Person; Cody Chastain; Laura Skaug; Lisa Rawn; Patty Wright (Association of American Medical Colleges, 2016)
Abstract Introduction Standardized patient simulation has become an essential tool for undergraduate and graduate medical education for both training and assessment of learners. It has been less consistently used for more advanced learners, including infectious diseases fellowship trainees. Methods Four standardized clinical scenarios were developed to provide an opportunity to observe infectious diseases fellows in a standardized clinical environment in order to evaluate history-taking, physical exam, diagnostic, and counseling skills. Case topics were chosen to emulate key encounters related to infectious diseases care. Full case descriptions, standardized encounter tools, and assessment rubrics were developed and implemented in concert with simulation experts and standardized patients from the Vanderbilt Center for Experiential Learning and Assessment. A faculty member observed each learner simulation, provided qualitative verbal and written feedback, and assessed learner performance utilizing assessment rubrics based on 5-point Likert scales. Results Between 2012 and 2015, 18 first- and second-year infectious diseases fellows were evaluated using the simulation, which was well accepted as an educational tool by both fellows and faculty. Implementation of these tools helped identify individual learner opportunities for improvement as well as common educational gaps that subsequently led to systemic program interventions. Discussion Standardized patient simulation provides an additional tool for fellow assessments as well as infectious diseases fellowship program evaluations. These cases may be used in other institutions to assess fellows or other learners, unify assessment across programs, or provide a template for alternative assessments.